Comparative Study between Conventional and Intelligent Methods for Controlling on Speed of DC .Shunt Motor - misanjas, Dr.Jabbar Raheem Rashed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Application of intelligent control methods offers the best solutions to Speed control of D.C. motors. Conventional control algorithms, though simple, have their limitations and fail in offering the required responses. In this paper, suggested a Wavelet Neural Networks (WNNs) as a powerful method to speed control of D.C.shunt motor. Feed Forward Wavelet Neural Network(FFWNN) is proposed. This method leads to enhance dynamic behavior of driving system for the motor and an immune to load disturbance. Also this proposed is compared with traditional method with conventional controller. The parameters of PID controller and suggested methods are optimized by using powerful tool is called Particle Swarm Optimization (PSO) algorithm. The D.C. shunt motor drive with FFWNN-PID controller through simulation results proves a good in the performance and stability compared with traditional approach.